Digital Organization Dan Lembaga Pendidikan - Adi, Arya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Seeing the current technological developments continue to experience a drastic increase. In the digital era that is happening now, some human activities involve electronics in helping their workers, this automatically creates a new lifestyle. Digitalization cannot be denied and has a big role in facilitating humans. So that today's technology is a human bridge to enter the digital era civilization. Digital organization is a process carried out by organizations to overcome challenges in the current era and a solution to the impact of the Covid-19 pandemic which requires that all activities outside the home be reduced so that digitalization is very helpful for managing all aspects of activities within the organization, as well as institutions This digital era education is to support the implementation of educational institution activities such as online teaching and learning so that activities in educational institutions can continue even though the Covid-19 pandemic is affected.